1978
DOI: 10.1017/s0022112078000774
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic flow of a vibrationally relaxing gas past a circular cone

Abstract: The steady supersonic flow of a vibrationally relaxing gas past a cone is studied using numerical methods. Near the tip of the cone the flow is obtained by means of a coordinate expansion and built on to this is a characteristic network used to obtain the remainder of the flow. Of particular interest is the development of the frozen shock at the tip into a relaxation-dominated wave at distances large compared with the width of the wave. The numerical results are presented in a concise similarity form which wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…So far, we have completed three investigations all dealing with the type of flow which leads to an ultimate shock wave which can be described by the steady-state approach discussed in 93. These are: the flow due to an impulsively started piston (Dain and Hodgson 197.5), the steady two-dimensional flow past a thin wedge (Hornby and Johannesen 1975), and the steady flow past a cone (Kao and Hodgson 1978). Work in progress includes the single finite pulse due to a piston and the N wave.…”
Section: Numerical Calculations Using the Methods Of Characteristicsmentioning
confidence: 99%
“…So far, we have completed three investigations all dealing with the type of flow which leads to an ultimate shock wave which can be described by the steady-state approach discussed in 93. These are: the flow due to an impulsively started piston (Dain and Hodgson 197.5), the steady two-dimensional flow past a thin wedge (Hornby and Johannesen 1975), and the steady flow past a cone (Kao and Hodgson 1978). Work in progress includes the single finite pulse due to a piston and the N wave.…”
Section: Numerical Calculations Using the Methods Of Characteristicsmentioning
confidence: 99%
“…Results indicated a considerable dispersion of the shock by the fog. Meanwhile, analytical methods incorporating characteristics networks were developed for the calculation of flows possessing vibrational relaxation regions (199)(200)(201)(202) (Fig. 20), the first of these by Kosh Mohammad (199) having been supervised by Ian Hall.…”
Section: The Department Of the Mechanics Of Fluids And Its Successorsmentioning
confidence: 99%
“…The translational and rotational modes are assumed to move through equilibrium states and the only dissipative mechanism outside shock waves is the non-equilibrium production of entropy due to the lag in the vibrational mode. Hornby & Johannesen (1975) and Kao & Hodgson (1978) considered steady wedge and cone flows, respectively, while Dain & Hodgson (1 975) treated the unsteady flow due to an impulsively started piston. The numerical calculations were carried out for a pure gas with large vibrational specific heat, but Hodgson & Johannesen (1 976) demonstrated that the calculations could be used to obtain tentative results relevant to air which has two vibrational modes, both with very small vibrational specific heats at meteorological temperatures, but with vastly different, strongly humidity-dependent, relaxation times.…”
Section: Introductionmentioning
confidence: 99%